Redescription of the tiger beetle Cicindelidia aeneicollis (Bates 1881) (Coleoptera: Cicindelidae) and discovery of new morphological variants from the Pacific Slope of Mexico - Duran, Daniel P.; Shetterly, John A.; Vogtsberger, Roy C. (Zootaxa, 2024)
The tiger beetle species, Cicindelidia aeneicollis (Bates 1881) is redescribed, as Bates’ original description was inadequate and did not accurately capture the character states or variation found within the species. The specific epithet ‘aeneicollis’ is partially misleading as the proepisternum is mostly aeneous (bronze/copper) with the basal quarter to third being polychromatic, which the description does not convey. Some populations of this species from the western coast of Mexico exhibit significant variation in maculations, with individuals ranging from weakly marked (as in Bates’ description) to much more extensively marked.